Trade and Industrial Policy for a 'Declining?' Industry: the case of the U.S. Steel Industry - Richard G. Harris (Queen's University, Department of Economics, 1990)
An intertemporal partial equilibrium model of the U.S. steel industry is developed which stresses imperfect competition, and the interaction between the large declining integrated steel producers and the entry of the new efficient mini-mills. A central question is whether trade and industrial policy should favour one sector at the expense of another. The existing policy of VRA's on steel is estimated to have a welfare cost of equal to 6.5 percent of the present value of base consumption. Furthermore, it is shown that the joint presence of imperfect competition and rent-shifting VRA's implies that a partial tightening of the steel quotas would lead of an improvement in national welfare which is quantitatively significant, even though free trade in steel is the globally optimal policy.
Keywords: 330